2013
DOI: 10.1016/s1734-1140(13)71476-2
|View full text |Cite
|
Sign up to set email alerts
|

BDNF rs 6265 polymorphism and COMT rs 4680 polymorphism in deficit schizophrenia in Polish sample

Abstract: The analysis of the COMT rs4680 polymorphism in the present DS and NDS study shows that some genetic factors may be relevant in analyzing the reasons for the differentiation of schizophrenic subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
2
19
0
1
Order By: Relevance
“…Our results are in agreement with the results of some authors who showed the absence of an associa tion of BDNF gene polymorphic loci with schizophre nia development in Japanese [25] and Poles [26]. On the contrary, other researchers were able to find asso ciations of the studied BDNF gene polymorphic loci with schizophrenia development [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with the results of some authors who showed the absence of an associa tion of BDNF gene polymorphic loci with schizophre nia development in Japanese [25] and Poles [26]. On the contrary, other researchers were able to find asso ciations of the studied BDNF gene polymorphic loci with schizophrenia development [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…Galderisi et al [223,224] found no association between the same polymorphism and either schizophrenia or its DS/ NDS subtypes. Pełka-Wysiecka et al [203] found a higher frequency of the Val158 allele in NDS subjects and no association of BDNF SNP with DS/NDS subtypes.…”
Section: Studies Of Genetic Risk For Ds or Empirically Identified Ds-mentioning
confidence: 96%
“…Some evidence suggests that the genetic basis of schizophrenia may differ between patients with distinct clinical profiles [199][200][201][202][203]. Genes might increase susceptibility to distinct clinical subtypes of the illness or may influence clinical features of the disease in a dimensional fashion, without altering liability to the illness itself (modifier loci).…”
Section: Genetic Studiesmentioning
confidence: 99%
“…According to our examination of the literature, the involvement of rs10770141 in the onset of schizophrenia has been suggested, but most of the prior studies failed to demonstrate a significant genetic association [25]. In addition, rs4680 has been reported to have a 8 significant association with schizophrenia [26], but this finding was not always supported [27]. The results of studies focusing on rs1800497 also indicated that its association with schizophrenia remains controversial [28,29].…”
Section: Discussionmentioning
confidence: 95%